Mediação informacional, políticas públicas e redes na atenção à saúde da mulher: a Casa de Parto David Capistrano Filho - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia - Universidade Federal do Rio de Janeiro, 2022)
The general objective of the present research is to understand informational and knowledge mediations, the formation of social networks and the formulation of public policies from the historical and socio-political processes that culminated in the creation and consolidation of the David Capistrano Filho Birth Center, in the city of Rio de Janeiro, emphasizing the importance of social mobilizations and intersectoral articulation for the qualification of the public health system. To achieve this objective, the following steps were taken: a) development of a Case Study methodology to understand, the from a historical-documentary research, the socio-historical processes that favored the existence and permanence of the CPDCF, as an institution of the SUS; b) mapping of info-communicational mediation processes in the construction of public policies, paying attention to the establishment and performance of collaborative networks in health. The results point to the centrality of the information object, as a conceptual potential for understanding social phenomena in health. Information practices, information flows, collaborative networks and mediations derived from informational processes constitute the sine qua non factor that enabled social and political mobilization actions, instituting a terrain of dispute for the recognition, in the scientific field, of knowledge not centered on the field of medicine, and in the social field of the incorporation of social knowledge, or those constructed in the field of culture and everyday life.
Keywords: Informação; Mediação; Redes Sociais; Políticas Públicas; Saúde da Mulher; Humanização do Parto; Information; Mediation; Social Networks; Public Policies; Women’s Health; Birth Humanization; Ciência da informação